part A)
![\bf \begin{array}{|c|cccccc|ll} \cline{1-7} x&8&27&64&125&&x\\ \cline{1-7} y&\stackrel{\sqrt[3]{8}}{2}&\stackrel{\sqrt[3]{27}}{3}&\stackrel{\sqrt[3]{64}}{4}&\stackrel{\sqrt[3]{125}}{5}&&\sqrt[3]{x} \\ \cline{1-7} \end{array}~\hspace{10em}y = \sqrt[3]{x}](https://tex.z-dn.net/?f=%5Cbf%20%5Cbegin%7Barray%7D%7B%7Cc%7Ccccccc%7Cll%7D%20%5Ccline%7B1-7%7D%20x%268%2627%2664%26125%26%26x%5C%5C%20%5Ccline%7B1-7%7D%20y%26%5Cstackrel%7B%5Csqrt%5B3%5D%7B8%7D%7D%7B2%7D%26%5Cstackrel%7B%5Csqrt%5B3%5D%7B27%7D%7D%7B3%7D%26%5Cstackrel%7B%5Csqrt%5B3%5D%7B64%7D%7D%7B4%7D%26%5Cstackrel%7B%5Csqrt%5B3%5D%7B125%7D%7D%7B5%7D%26%26%5Csqrt%5B3%5D%7Bx%7D%20%5C%5C%20%5Ccline%7B1-7%7D%20%5Cend%7Barray%7D~%5Chspace%7B10em%7Dy%20%3D%20%5Csqrt%5B3%5D%7Bx%7D)
part B)
f(x) = 10 + 20x
so if you rent the bike for a few hours that is
1 hr.............................10 + 20(1)
2 hrs..........................10 + 20(2)
3 hrs..........................10 + 20(3)
so the cost is really some fixed 10 + 20 bucks per hour, usually the 10 bucks is for some paperwork fee, so you go to the bike shop, and they'd say, ok is 10 bucks to set up a membership and 20 bucks per hour for using it, thereabouts.
f(100) = 10 + 20(100) => f(100) = 2010.
f(100), the cost of renting the bike for 100 hours.
Answer:
The new amount paid to mechanics per after by new owner is $ 19 Answer
Step-by-step explanation:
Given as :
The amount paid to mechanics initially = $ 20 per hour
Now, The new owner paid less at the rate = 5%
Let the amount paid to the mechanics after 5 % less = x per hour
So, According to question
The new amount paid to mechanics per hour = initial amount paid per hour × ( 1 -
)
or, The new amount paid to mechanics per hour = $ 20 × ( 1 -
)
I.e The new amount paid to mechanics per hour = $ 20 × 0.95
∴ The new amount paid to mechanics per hour = $ 19
Hence The new amount paid to mechanics per after by new owner is $ 19 Answer
The answer would be 89.90558242
If u round it off, the answer will be 90
Number of cubes increases by 3 for each term.
an= 3n+1
The ratio of height : shadow =44/1313
Therefore height of the tree,x=3434*(44/1313)
=115.08 ft
If you meant 13 and 34 as the length of shadows respectively, then also x=115.08 ft